Implementation of Performance Assessment in Financial Literacy Materials within Social Studies Learning to Foster A Financially Literate Generation at SMP Yadika 2 - Qiden Binta Raifadilah; Mamat Ruhimat; Dina Siti Logayah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to implement performance assessment through individual poster-making tasks in financial literacy materials within Social Studies (IPS) learning. A quantitative approach with a descriptive method was applied. The population consisted of seventh-grade students at SMP Yadika 2, while the sample was selected using a random sampling design, namely class VII B. Data were collected through observation, documentation, and assessment based on six indicators: conceptual understanding, accuracy of information, design creativity, readability, independence, and content relevance. Data were analyzed using descriptive statistics. The results showed that 42 students obtained scores ranging from good to very good, particularly in creativity and conceptual understanding. However, several students still faced challenges in delivering information accurately and in-depth. Performance assessment was proven to enhance students’ engagement and their skills in conveying messages through visual media. This model can be applied as a meaningful project-based learning strategy to strengthen financial literacy in secondary school students.